Reciprocity and job mobility: The effect of effort-reward imbalance in the employer-employee relationship on turnover intentions and actual job changes - Prechsl, Sebastian (Social Science Research, 2025)
Numerous studies illustrate that a lack of reciprocity between effort and reward in the employer-employee relationship produces negative effects on employees’ health and well-being. This might motivate employees to change jobs as a consequence. Based on German panel data with 16,243 observations from 4,641 employees, I analyze the effect of effort-reward imbalance (ERI) on turnover intentions and actual job changes and whether health-threatening ERI exposure affects the realization of job changes. The results indicate more frequent doctor visits, lower job satisfaction, higher turnover intentions, and higher job change probabilities when employees’ efforts in relation to rewards increase. The ERI effects on turnover intentions and job changes are both mediated through job satisfaction. Finally, I find no evidence that ERI exposure moderates the relationship between turnover intentions and actual job changes.<br
Keywords: Effort-reward imbalance Employer-employee relationship Health Job change Job satisfaction Panel data Reciprocity Turnover intentions